(untitled) (World Bulletin of Social Sciences, 2023)
The Akashat area of the town of Al-Walid within the city of Al-Rutba, in the far west of the Iraqi province of Anbar, includes the largest phosphate mines in the country, which before the US invasion of the country in 2003 was one of the main mining spots besides oil and gas, providing the needs of internal demand. Before the first Gulf War in 1991, Iraq was exporting phosphate to East and Northeast Asian countries and several European countries, but the hand of neglect and terrorism represented by the “American occupation” and then the invasion of “ISIS” organization, Anbar Governorate, caused the destruction of the infrastructure in the mines, which contributed to companies Yugoslavia in the seventies of the last century developed at that time. Therefore, the mines as a whole suffer "from government neglect from Baghdad, which made it an abandoned area, in addition to the fact that the control of armed parties over the area hinders the completion of any operation to invest the mine, which is owned by the Ministry of Industry." "The Iraqi Ministry of Industry and Minerals refused to accept several offers to invest in mines by a British company, and despite the company’s attempts to obtain the ministry’s approval, over the past five years, it failed." Therefore, we find that “the facilities affiliated to the Ministry of Industry and Minerals in Anbar suffer complete neglect, especially the Akashat phosphate mines, which have been shut down since 2003, although the imports that come from the mine, if it is operational, are not less than the oil export imports that the Iraqi government relies on to finance. Government Budget". Therefore, we find that "investment in such major mines or factories is done through the central government and the Geological Survey Company, and local governments are not allowed to approve investment or not, not even to deal with investors." He stressed that "the local government in Anbar has approached several times in order to invest the Akashat mines, but the Ministry of Industry and Minerals is like a dead man ".